Structural evolution of long‐duration meteor trail irregularities driven by neutral wind. Issue 12 (9th December 2014) - Li, Guozhu; Ning, Baiqi; Chu, Yen‐Hsyang; Reid, I. M.; Hu, L.; Dolman, B. K.; Xiong, J.; Jiang, G.; Yang, G.; Yan, C.
Abstract: An experiment on spatial domain interferometry observations of meteor trail irregularities at a low‐latitude location in China was conducted during August 2013 using the Sanya VHF coherent radar (18.4°N, 109.6°E). More than 3 thousand range‐spread meteor trail echoes (RSTEs) were observed. Among the trail echoes, the spatial structure of meteor trail irregularities responsible for a single long‐duration RSTE event persisting for ~4 min was reconstructed. This RSTE was found to be initially generated at 90–115 km altitudes and aligned along the radar beam boresight. After about the first minute of the trail lifetime, the trail echo appeared only in a narrow altitude range of 94–98 km. An analysis on the spatial pattern of the long‐duration RSTE showed that the trail irregularities at lower range gates moved away from the region perpendicular to the geomagnetic field. The eastward drifts of the RSTE irregularities were found to decrease with increasing altitude, e.g., from 80 ms −1 at ~94 km to 20 ms −1 at ~100 km. Simultaneous horizontal neutral wind measurements made with the Fuke all‐sky meteor radar (located north of Sanya) recorded a similar velocity profile. We suggest that the neutral wind could drive the spatial structural evolution of the RSTE irregularities, and help to determine the altitudes where the longest portion of the RSTE was located. Key Points: The Sanya radar interferometry observation of a long‐duration meteor trail The trail structural evolution from strip type to layer type is detected Factors responsible for the characteristics of long‐duration trail are studied